Labels on apples: winners and losers - Batt, Peter; Sadler, C. (Australian New Zealand Marketing Academy. University of New South Wales, 1999)
Retailers, in particular the large supermarket chains, are the driving force behind the need for fruit growers in Australia to individually label apples. By labelling apples with either the variety name or a price look-up (PLU) number, check-out staff can identify the variety quickly, price it accordingly and minimise the amount of error made. Such allows retailers to offer consumers a wider choice of varieties. While fruit must be labelled in order to supply the large retail chains, the majority of growers, wholesale market agents, retailers and consumers do not believe that labels are any indication of better quality fruit. Nor is there any indication of labelled apples achieving a price premium, despite the additional costs. The failure of fruit growers to adhere to quality standards, poor post-harvest management, immature fruit and the lack of quality control throughout the distribution channel is responsible for the poor quality of labelled fruit offered for sale in Perth retail stores.